1998
DOI: 10.3171/jns.1998.89.5.0762
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous sinus sampling in patients with adrenocorticotrophic hormone—dependent Cushing's syndrome with emphasis on inter- and intracavernous adrenocorticotrophic hormone gradients

Abstract: These results suggest that 1) cavernous sinus sampling without CRH administration can demonstrate hypersecretion of ACTH from the pituitary gland with a high diagnostic accuracy; 2) intercavernous gradients will indicate the correct lateralization in laterally localized microadenomas; and 3) sampling should be performed from the posterior portion of the cavernous sinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 31 publications
2
31
0
3
Order By: Relevance
“…On the other hand, Teramoto et al described the usefulness of CSS compared to IPSS and suggested that the tentative cutoff ratio is 5 for the diagnosis of pituitary lesions [19]. In our case, we obtained a ratio of greater than 5 in left cavernous sinus and fortunately the origin of excessive ACTH was in the pituitary gland.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…On the other hand, Teramoto et al described the usefulness of CSS compared to IPSS and suggested that the tentative cutoff ratio is 5 for the diagnosis of pituitary lesions [19]. In our case, we obtained a ratio of greater than 5 in left cavernous sinus and fortunately the origin of excessive ACTH was in the pituitary gland.…”
Section: Discussionsupporting
confidence: 51%
“…The accuracy of determining lateralization by means of bilateral inferior petrosal sinus sampling is reported to be approximately 75% [28], and that by means of bilateral CSS ranges widely from 40% to 94% [19,29,30]. In this case, the basal left-to-right gradient showed 1.24, but the normalized ACTH/PRL left-to-right gradient showed 1.34, which was near 1.4.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Correct lateralization has been reported to be 57%-80% 15,16 and can also distinguish between central and ectopic sources of ACTH oversecretion.…”
Section: Discussionmentioning
confidence: 99%